Visual Function in Older Eyes in Normal Macular Health: Association with Incident Early Age-Related Macular Degeneration 3 Years Later - Owsley, Cynthia (Invest Ophthalmol Vis Sci, 2016)
PURPOSE: In older eyes in normal macular health, we examined associations between impaired photopic acuity, mesopic acuity, spatial contrast sensitivity, light sensitivity, and the presence of low luminance deficit (difference between photopic and mesopic acuity) at baseline and incident AMD 3 years later. Associations were compared with an association between delayed rod-mediated dark adaptation and incident AMD, previously reported for this cohort. METHODS: Enrollees were 60 years or older. Eyes at step 1 in the AREDS nine-step classification system based on masked grading of color fundus photographs were included. Photopic and mesopic acuity, contrast sensitivity, and light sensitivity, and the presence of low luminance deficit, were measured at baseline. Demographic, lifestyle, general health, and blood markers were assessed at baseline as potential confounders. Three years later fundus grading was repeated to determine AMD presence. RESULTS: For the analysis, 827 eyes of 467 persons were eligible. Impaired mesopic acuity at baseline was associated with incident AMD, age-adjusted rate ratio (RR) 1.57 (95% confidence interval [CI] 1.04–2.35), whereas impaired photopic acuity, contrast sensitivity and macular light sensitivity, and the presence of a low luminance deficit were not. The mesopic acuity association was slightly weaker than the association between abnormal dark adaptation and incident AMD (RR 1.85, 95% CI 1.07–3.20). CONCLUSIONS: Impaired mesopic acuity in eyes in normal macular health is a risk factor for incident early AMD 3 years later, however, photopic acuity, contrast sensitivity, and light sensitivity, and the presence of a low luminance deficit are not risk factors.